1993
DOI: 10.1111/j.1540-8191.1993.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Semilunar Valve Replacement with a Cylindrical Valve

Abstract: A cylindrical valve was designed to prevent regurgitation of the semilunar valve. The valve is made of a sheet of polytetrafluoroethylene (PTFE) or porcine pericardium, and has three cusps and three commissures. The diameter of the valve is equal to the height of the cusps. We have used these valves in pulmonary stenosis after Jatene's operation and total correction of tetralogy of Fallot, and for truncal valve regurgitation. Regurgitation was trivial on color Doppler echocardiography in all cases. Advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The monocusp RVOT patch can be created with autologous or bovine pericardium,[8] allograft pulmonary valve cusp,[9] or with PTFE membrane. [21011]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monocusp RVOT patch can be created with autologous or bovine pericardium,[8] allograft pulmonary valve cusp,[9] or with PTFE membrane. [21011]…”
Section: Discussionmentioning
confidence: 99%
“…Yamagishi and Kurosawa[10] and Oku and colleagues[11] introduced 0.1-mm PTFE for monocusp valve construction in 1993. Animal studies suggested that 0.1-mm PTFE functioned better than fresh or glutaraldehyde-treated pericardium for monocuspid valve construction.…”
Section: Discussionmentioning
confidence: 99%
“…The bovine pericardial patch may cause inflammation and fibrosis in the native valve, impeding its growth. Valve patches made of a different material, such as polytetrafluoroethylene, [10][11][12] or use of a homologous decellularized pulmonary valve cusp 13 may further improve long-term valve performance. The observed hospital mortality, 6.8%, is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…The monocusp RVOT patch can be created with autologous or bovine pericardium, 4,5 allograft pulmonary valve cusp, 6 or the (off label) use of a polytetrafluoroethylene (PTFE) membrane (0.1-mm PTFE patch; W. L. Gore & Associates, Inc, Flagstaff, Ariz) traditionally used for pericardial closure. [7][8][9] All types of monocusps have shown, particularly in the immediate postoperative period, to significantly reduce or prevent pulmonary insufficiency (PI). 10 The elimination of PI is associated with faster recovery of RV function, a lower central venous pressure, and less postoperative chest tube drainage.…”
mentioning
confidence: 99%